Dreiser's "Jennie Gerhardt" : New Essays on the Restored Text - West, James L. W. (Book collections on Project MUSE., 1995)
In 1992 the University of Pennsylvania Press published a new edition of Theodore Dreiser's second novel, Jennie Gerhardt. The original published text was altered significantly from the author's intentions: its sexual energy was short-circuited, its criticisms of organized religion were blunted, its language was smoothed and sentimentalized, and, most important, Jennie Gerhardt was reduced to a less thoughtful, less womanly character. The restored edition brings back the sexual charge, reinstates the social and religious criticism, and makes the language Dreiser's again.This volume brings together 19 fresh readings, together with an introduction, of the Pennsylvania edition by three generations of Dreiser critics. The volume includes general assessments, analysis of main characters, treatments of the autobiographical roots of the narrative, views of various traditions (realistic, sentimental, ethnic) on which Dreiser drew, and investigations of historical contexts that inform his story.